Memorandum to Councilwoman Jane Tolmach from Stephen A. Cook - Stephen A. Cook:::::: (1976)
This April 6, 1976 City of Oxnard memorandum to Councilwoman Tolmach transmits background materials regarding AB 15, the California Agricultural Lands Act. Included are summaries of Assemblyman Charles Warren's proposed modifications, correspondence from the League of California Cities, and detailed letters from Oxnard officials outlining strong concerns about the bill. While Warren's revisions sought to address issues such as mapping requirements, vested rights, and revenue impacts, Oxnard officials argued the bill remained overly restrictive and arbitrary, particularly for a city surrounded by prime agricultural land. The City warned that AB 15 could block development of schools, parks, industrial projects, infrastructure, and planned neighborhoods, while also threatening local revenue and undermining local land-use authority. The League proposed amendments to allow urban service boundaries, municipal flexibility, state reimbursement of costs, and representation on the Agricultural Council, and committed to working with Warren to revise the bill before Senate consideration.